Evaluation of Mangrove Water Quality in Pancer Cengkrong, Trenggalek and Sine, Tulungagung, East Java, Indonesia Using Phytoplankton as Bioindicators - Satria Cahya Febriansyah; Luchman Hakim; Catur Retnaningdyah (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight Research Anthropogenic factors are the main cause of damage to mangrove ecosystems Restoration is a method for ecosystem restoration Restoration success is seen from the physical, chemical, and biological parameters Phytoplankton is a bioindicator of water quality The abundance of mangroves can explain the state of an ecosystem   Abstract Mangrove ecosystems in Sine and Pancer Cengkrong had degraded due to land-use change and restoration has been carried out over a few year on the damaged location. This study was conducted to evaluate water quality of mangrove ecosystems at both locations based on physical, chemical and phytoplankton parameters as bioindicators. The evaluation of Cengkrong Mangrove was carried out at 4 different locations based on different periode of restoration, namely restoration of 2008-2009, 2013-2014, natural mangroves, and 2005 succession mangroves, whereas there was only one sampling site at Sine mangrove namely 1998-2008 restoration. The physico-chemical parameters measured include water temperature, air temperature, conductivity, pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), salinity, nitrate, and orthophosphate. Phytoplankton data was used to measure, trophic diatom index (TDI) as an indicator of water nutrition status, and pollution tolerant value (%PTV) as an indicator of organic pollution. The results showed that the water quality at all the study locations met the Indonesian Ministry of Environment Regulation No 51/2004, except nitrate and phosphate. Based on the TDI index, mangrove in Sine, Cengkrong 2013-2014 restoration, and 2005 succession mangroves were categorized as hyper-eutrophic, natural Cengkrong mangroves were categorized as eutrophic, and 2008-2009 restored Cengkrong mangroves were categorized as meso-eutrophic. Based on the %PTV index, in the Sine mangrove, 2013-2014 Cengkrong restoration, and 2005 succession mangroves were classified as high levels of organic matter pollution, while in the Cengkrong 2008-2009 restoration and natural Cengkrong were classified as a moderate level of organic pollution.